FASADE ARSITEKTUR, NAMA DAN PENEMPATAN UKIRAN TRADISIONAL MINANGKABAU PADA SURAU TUO NAGARI LUBUAK BAUAK KECAMATAN BATIPUAH KABUPATEN TANAH DATAR - Drs. Erfahmi, M.Sn., ADITYA ARMIN, Ir. Drs. Heldi, M.Si. Ph.D., (Serupa The Journal of Art Education, 2017)
Surau is the work of traditional architecture in the form of artifacts built from society or civilization culture in Minangkabau. The main function of the surau for the society of minangkabau of culture as a place of worship, education and in addition as a place of preservation of culture as learned silat and randai. Architectural form and space fields have a surau which are filled with aesthetic element-element such as carving and art elements to a field of facade the facade areas. Have the spaces and elements containing score organize social order Minangkabau society life. As the study in this research can be formulated research question what are the elements and the elements that are contained in the fasade fields of space or the name and its placement. The research objectives are: 1. Explain facade villge surau Lubuak Bauak. 2. The name describes the traditional carving minangkabau that there exist in the village surau tuo Lubuak Bauak. 3. Explain the placement of carving traditonal Minangkabau contained in this facade research located in the village Batipuah Baruah Batipuah Lubuak Bauak districts Batipuah Tanah Datar. Research is qualitative discriptive approach. Research done by the spaciousness observation, interviews, and collecting documentation. For data collection and analysis, by the way educations, data presentation and conclusion. To test the validity of the data is done by triangulation. The research found the artifact facade there are four areas, namely the position of facade front, right and left side of the field behind. All fours sides of the facade surface are the names of carving and placing the same on each field. There are twenty names carving and included a motif under the influence of the nederlands. All the names and form of this engraving made in the field of small big and placed vertically, horizontally and diagonaly across the entire surface of the facade.Kata kunci: Fasade, Ukiran, Penempatan, Tradisional, Surau Tuo